The Competition Commission's non-referral of exclusivity clauses in the shopping centre lease context: a monumental misjudgement - A Section 5(1) analysis of anticompetitiveness - Blumenthal, Roxanne (Department of Commercial Law, 2015)
This paper focuses on the common practice in commercial agreements of including exclusivity clauses in shopping centre lease agreements between a supermarket anchor tenant and the landlord of a shopping centre. It is the contention of this paper that such clause s are anticompetitive when considered specifically in light of section 5(1) of the South African Competition Act. In reaching this conclusion, relevant sect ions of the Act will be interpreted and analysed in the pertinent context, as will relevant case law and comparable foreign jurisprudence. The findings of South Africa's Competition Commission in 2013 with regard to the competitive nature of exclusivity clauses in the context of section 5(1), and the basis for their findings will be scrutinised. A conclusion , warranted and supported by the inferences drawn from an analysis of the aforementioned sources (legislation, case law and foreign jurisprudence), will be reached accordingly in support of a stance of resistance against exclusivity clauses in shopping centre leases between landlord and supermarkets . An argument in favour of a blanket prohibition of exclusivity clauses in shopping centre leases due to their anticompetitive nature that outweighs their efficiencies and justifications according to section 5(1) of the Act, is the predominant direction of this paper.